FROM KHILÂFAH TO MODERN STATE: The History of Islamic Political Transformation - Fata, Ahmad Khoirul; Adnan, Adnan; Fauzi, Mahfud (ULUL ALBAB Jurnal Studi Islam, 2021)
This article discusses the dynamic and changes in Islamic political history. Rather than focuses on the Islamic doctrine, it focuses on the characteristics of each historical period. Through historical approach, this study reveals that Islam and state-politics are two sides of a coin. Since the beginning of Islam, it has been intertwined with state politics. Nevertheless, the history of Islamic politics has many faces. There is no standard shape or entity of Islamic politics. Changes and variation are the result of the Islamic ummah’s efforts to develop political institutions that suit the demand of the era while trying to adhere to the Islamic teachings. This dynamic is seen in the changes from the era of the Prophet PBUH, the era of the four main Caliphs, up to the era of the large dynasties. In this modern era, the Islamic politics experiences a crisis due to the downfall of the old Islamic political entity (the caliphate) and the interaction with the modern west-political ideas. Various thoughts and political concepts tries to provide answers for the appropriate Islamic political shape/entity for this new era. However, currently a standard and ideal shape for an Islamic political entity is yet to be found.